Circadian Clock Gene Expression in the Coral Favia fragum over Diel and Lunar Reproductive Cycles - Hoadley, Kenneth D. (Public Library of Science, 2011)
Natural light cycles synchronize behavioral and physiological cycles over varying time periods in both plants and animals. Many scleractinian corals exhibit diel cycles of polyp expansion and contraction entrained by diel sunlight patterns, and monthly cycles of spawning or planulation that correspond to lunar moonlight cycles. The molecular mechanisms for regulating such cycles are poorly understood. In this study, we identified four molecular clock genes (cry1, cry2, clock and cycle) in the scleractinian coral, Favia fragum, and investigated patterns of gene expression hypothesized to be involved in the corals' diel polyp behavior and lunar reproductive cycles. Using quantitative PCR, we measured fluctuations in expression of these clock genes over both diel and monthly spawning timeframes. Additionally, we assayed gene expression and polyp expansion-contraction behavior in experimental corals in normal light:dark (control) or constant dark treatments. Well-defined and reproducible diel patterns in cry1, cry2, and clock expression were observed in both field-collected and the experimental colonies maintained under control light:dark conditions, but no pattern was observed for cycle. Colonies in the control light:dark treatment also displayed diel rhythms of tentacle expansion and contraction. Experimental colonies in the constant dark treatment lost diel patterns in cry1, cry2, and clock expression and displayed a diminished and less synchronous pattern of tentacle expansion and contraction. We observed no pattern in cry1, cry2, clock, or cycle expression correlated with monthly spawning events suggesting these genes are not involved in the entrainment of reproductive cycles to lunar light cycles in F. fragum. Our results suggest a molecular clock mechanism, potentially similar to that in described in fruit flies, exists within F. fragum.